Swelling behaviour of expansive soils with recycled geofoam granules column inclusion. Issue 1 (February 2019) - Selvakumar, S.; Soundara, B.
Abstract: Structures founded on expansive soils experience large uplift pressure due to the high swelling nature of these soils. In this investigation, an effort is taken to reuse the waste expanded polystyrene (EPS) beads to form geofoam granules column (GGC) and quantify the swelling behaviour of expansive soil with and without GGC inclusion. Several swell tests were carried out in statically compacted soil specimen with uniform thickness of 100 mm placed in a large scale one dimensional consolidation apparatus which can accommodate the California bearing ratio (CBR) mould. Attempts were made to ascertain the performance of GGC inclusion in expansive soil by varying diameters of GGC (25 mm, 40 mm, 50 mm and 75 mm), density of formed GGC (15 kg/m 3 and 20 kg/m 3 ) and two placement conditions of soil samples (by varying moisture content). Tests results were analysed which showed that the percentage of swell, swelling pressure and the time rate of swell decreases upon inclusion of GGC and significant reduction is noticed for lesser GGC density. Further, the mechanism of GGCs influence in control swelling of expansive soil is explained with the help of soil-GGC interaction.